Maximum power point tracking technique based on optimized adaptive differential conductance. Issue 1 (1st January 2017) - Eze, Val Hyginus U.; Iloanusi, Ogechukwu N.; Eze, Martin C.; Osuagwu, Charles C.
Abstract: Maximum power point (MPP) tracking technique based an optimized adaptive differential conductance technique was developed in this paper. The performance of the algorithm developed in this paper was evaluated at solar irradiance of 1, 000, 800 and 600 W/m 2 and at temperature of 298, 328 and 358 K. From the simulation results, it was observed that the impedance of the panel decreases as the irradiance increases while the impedance of the load is not affected by the irradiance. This technique was also validated with conventional incremental conductance (INC) technique. From the validation result, the resultant conductance of the optimized adaptive differential conductance technique at MPP is 0.0030 mho higher than resultant conductance at ideal condition while conventional technique has the resultant conductance of 0.0418 mho lower than the resultant conductance at ideal condition. From the analysis, the technique has a relative improvement of 6.0558% compared to the conventional INC technique. The simulation was done using Matrix Laboratory (MATLAB).